Some features of depressive disorders under the pain syndrome after the herniation of invertebral disk surgical treatment - S. A. Fedyanin; A. S. Fedyanin; I. V. Smagina; Yu. V. Lichenko; Ye. A. Dorokhova (Бюллетень сибирской медицины)
Checkup of 215 patients with pain syndrome relapse in the late period of the diskectomy. Middle age (45,6 ± 0,6) years. The patients were examined: neurological status, lumbar spine radiography, magnetic resonance imaging procedure. Depression revealed by Zung scale. Revealed depressive disorders occur in 47% patients. Mild and masked depression predominates. Depressive disorders occur mainly in the disk herniation relapse in operated and adjacent segments, by spinal canal stenosis and cicatricial-commissural epiduritis. Post-discharge adjustment in patients with pain syndrome relapse in the late postoperative period must be carry out consider depressive disorders.